2007
DOI: 10.1007/s10260-007-0076-2
|View full text |Cite
|
Sign up to set email alerts
|

Modelling individual fertility levels in Malawian women: a spatial semiparametric regression model

Abstract: Bayesian, Children ever born, Clustering, Fertility levels, Malawi, Poisson regression, Spatial modelling,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
(50 reference statements)
3
23
0
Order By: Relevance
“…The results obtained using the naive approach show that the education-fertility relationship follows a non-linear decreasing trend that is particularly strong for women with more than eight years of education. This pattern confirms the findings of Kalipeni (1997) and Kazembe (2009).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The results obtained using the naive approach show that the education-fertility relationship follows a non-linear decreasing trend that is particularly strong for women with more than eight years of education. This pattern confirms the findings of Kalipeni (1997) and Kazembe (2009).…”
Section: Resultssupporting
confidence: 91%
“…Scholars have observed that births usually occur within marriage in developing countries (e.g., Martin, 1995;Manda and Meyer, 2005;Kazembe, 2009). In the present study, we have not considered the woman's age at marriage.…”
Section: Observed Confoundersmentioning
confidence: 99%
See 3 more Smart Citations